Can teacher-child relationships support human rights to freedom of opinion and expression, education and participation? - Wang, Cen; Harrison, Linda; McLeod, S; Walker, Sue; Spilt, Jantine L (My University, 2018)
This study explored how teacher-child relationships change over the early school years, in terms of closeness and conflict, whether these trajectories differ in type and frequency for children with typical development and children with speech and language concern (SLC), and whether the trajectories are associated with school outcomes at 12-13 years.
International Journal of Speech-Language Pathology
Keywords: Article 19; United Nations; Universal Declaration of Human Rights; literacy achievement; school adjustment; speech and language concern; teacher–child relationship; Childhood and child development; Learning, education and training